(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
Due to the increase of the human population, it becomes indispensable increase food production, through an efficient maximization of the different agricultural resources. In this same sense, in the departments of Meta and Vichada, Colombia, located in low tropics, the productive yields are low and therefore the profitability is minimal or null in the livestock sector, condition that certainly does not stimulate the increase of production nor the establishment of grasses for grazing, on the other hand, if it makes the land that was especially cattle-raising, they are sowing crops like: timber, palm, rubber, cane, corn and soybeans. The pastures are the main source of food for ruminants, they are grown and managed like any other plant, and well established, allow to supply a large number of animals per unit área, situation that was considered in the high undulating plain and mountainous area in which the farms are assisted, being categorized their soils as oxisols, which have on average a pH of 4.5, low availability of Ca, Mg, K, P, aluminum saturation greater than 65% and are susceptible to degradation. Therefore, it is decided to use a recommended amendment for nutrient-deficient soils that contains: dolomite lime, gypsum and phosphoric rock. In the establishment and / or renewal of pastures, supervision and monitoring was constant to the lots planted, which helped to correct the problems that arose during this activity, it also allowed decisions to be made on time, because in the establishment of the prairies should be managed improvised as rain, availability of machinery, and development of plants, among others, that must be properly resolved according to plan, avoiding generating additional costs. The application of amendments does not have to be only to correct soils with deficiencies, as are the farms in this area, but also incorporate minerals as nutritional constituents, since the quantity, composition and quality of the amendment will be reflected in the future in the prairies.